Sport and Fitness in Children and Adolescents - A Multidimensional View 2023
DOI: 10.5772/intechopen.106812
|View full text |Cite
|
Sign up to set email alerts
|

Sports Participation in South African Schools. Have We Lost the Plot?

Abstract: In view of global health concerns about elevated levels of inactivity and related disease patterns of citizens, policy reform in physical education and school sport (PESS) is seen as a basic human right and tool for societal transformation. Although literature supports the importance of quality PESS for different aspects of learners’ development, various implementation challenges facing school sports in South Africa have been reported. Drawing on a nationwide research project, this paper seeks to provide empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…The finding was consistent with that of Vosloo and du Toit 18 who found that sports in Township and rural schools were primarily facilitated by unqualified, untrained and inexperienced educators who are keen to be involved in such a sport, and in most cases, the dominant sport offered in such schools being football. This is exacerbated by a need for more human (qualified coaches/trainers), financial, physical (sports facilities and equipment), safety (protection from crime and gangsterism) and information resources that would enable an environment for sports participation in Township schools.…”
Section: Lack Of Sport At the Foundation Level And Dysfunctional Scho...supporting
confidence: 88%
See 3 more Smart Citations
“…The finding was consistent with that of Vosloo and du Toit 18 who found that sports in Township and rural schools were primarily facilitated by unqualified, untrained and inexperienced educators who are keen to be involved in such a sport, and in most cases, the dominant sport offered in such schools being football. This is exacerbated by a need for more human (qualified coaches/trainers), financial, physical (sports facilities and equipment), safety (protection from crime and gangsterism) and information resources that would enable an environment for sports participation in Township schools.…”
Section: Lack Of Sport At the Foundation Level And Dysfunctional Scho...supporting
confidence: 88%
“…The finding was supported by those of Vosloo and Du Toit 18 who reported that community sports complexes in low-income communities were supposed to facilitate school sports activities but are poorly maintained with overgrown grass, had poor ablution facilities and some were also rendered unsafe for use because of crime and gangsterism in the areas. Coaches highlighted a need for multipurpose-sport facilities in HDA to allow for a diverse range of sporting codes.…”
Section: Insufficient Sports Facilities and Transport Systemmentioning
confidence: 68%
See 2 more Smart Citations
“…The effective delivery of physical education in these schools is further hindered by high teacher workload, large class sizes, and insufficient funds. Additionally, limited opportunities for physical activity stem from the absence of, or inaccessibility to, organized sports, activity clubs, or chances for outdoor play [ 31 ].…”
Section: Methodsmentioning
confidence: 99%